Semantic web services theory, tools, and applications - Cardoso, Jorge 1970- (Gale virtual reference library, 2007)
Brings together researchers, scientists, and representatives from different communities to study, understand, and explore the theory, tools, and applications of the semantic Web. Joins the semantic Web, ontologies, knowledge management, Web services, and Web processes into one fully comprehensive resource, serving as the platform for exchange of both practical technologies and research.